Integrated European Polar Research Programme - ANDERSEN, Signe Bech; CHRISTENSEN, Torben R; ABELE, Doris; DANNEVIG, Halvor; NJÅSTAD, Birgit; MACELLONI, Giovanni (Zenodo, 2020)
TheEuropean Polar Research Programme is the outcome of a five-year process of co-designing and co-developing a future research agenda for Europe which has been performed within the EU-PolarNet consortium. One of the challenges consisted in the careful collection of the highly diverse polar stakeholder needs by implementing a series of engagement actions. Another key challenge was to translate these needs into prioritised research questions. This work was achieved by involving a wide range of polar experts and combining their expertise. In addition, the European Polar Research Programme was subject to a thorough review by different scientific and polar specialists in and outside the EU-PolarNet consortium. The European Polar Research Programme is organised in six main chapters dealing with overarching, cross-cutting research issues which should lead to major advances in the understanding of the Polar Regions. In total, the chapters highlight a number of research issues ranging from improved characterisation and understanding of the physical, environmental, societal, cultural and economic conditions, and the current changes and evolutions in the Polar Regions to better definition, prediction and projection of their future conditions, thus supporting adaptation and resilience to the changes. Major challenges identified in the EPRP relate to the actual implementation of research in terms of co-creation of knowledge, leveraging resources and enhanced international cooperation for the benefit of society at large. : Citation: EU-PolarNet (2020) Integrated European Polar Research Programme (Eds. Velázquez D, Houssais MN, Biebow N). 91 pp. Bremerhaven: Alfred Wegener Institute Visit us on: www.eu-polarnet.eu; Follow us on Twitter: @EUPolarNet